Interplay between intergrin-linked kinase and ribonuclease inhibitor affects growth and metastasis of bladder cancer through signaling ILK pathways. Issue 1 (December 2016) - Zhuang, Xiang; Lv, Mengxin; Zhong, Zhenyu; Zhang, Luyu; Jiang, Rong; Chen, Junxia
Abstract Background Integrin-linked kinase (ILK) is a multifunctional adaptor protein which is involved with protein signalling within cells to modulate malignant (cancer) cell movement, cell cycle, metastasis and epithelial–mesenchymal transition (EMT). Our previous experiment demonstrated that ILK siRNA inhibited the growth and induced apoptosis of bladder cancer cells as well as increased the expression of Ribonuclease inhibitor (RI), an important cytoplasmic protein with many functions. We also reported that RI overexpression inhibited ILK and phosphorylation of AKT and GSK3β. ILK and RI gene both locate on chromosome 11p15 and the two genes are always at the adjacent position of same chromosome during evolution, which suggest that ILK and RI could have some relationship. However, underlying interacting mechanisms remain unclear between them. Here, we postulate that RI might regulate ILK signaling pathway via interacting with ILK. Methods Co-immunoprecipitation, GST pull-down and co-localization under laser confocal microscope assay were used to determine the interaction between ILK and RI exogenously and endogenously. Furthermore, we further verified that there is a direct binding between the two proteins by fluorescence resonance energy transfer (FRET) in cells. Next, The effects of interplay between ILK and RI on the key target protein expressions of PI3K/AKT/mTOR signaling pathway were determined by western blot, immunohistochemistry and immunofluorescence assay in vivo and in vitro. Finally, the interaction was assessed using nude mice xenograft model. Results We first found that ILK could combine with RI both in vivo and in vitro by GST pull-down, co-immunoprecipitation (Co-IP) and FRET. The protein levels of ILK and RI revealed a significant inverse correlation in vivo and in vitro. Subsequently, The results showed that up-regulating ILK could increase cell proliferation, change cell morphology and regulate cell cycle. We also demonstrated that the overexpression of ILK remarkably promoted EMT and expressions of target molecules of ILK signaling pathways in vitro and in vivo. Finally, we found that ILK overexpression significantly enhanced growth, metastasis and angiogenesis of xenograft tumor; Whereas, RI has a contrary role compared to ILK in vivo and in vitro. Conclusions Our findings, for the first time, directly proved that the interplay between ILK and RI regulated EMT via ILK/PI3K/AKT signaling pathways for bladder cancer, which highlights the possibilities that ILK/RI could be valuable markers together for the therapy and diagnosis of human carcinoma of urinary bladder.